Agronomic performance of lettuce with different organic substrates and shadows - Silva, Antônio Veimar da (2020)
The objective of this work was to evaluate the effects of different organic substrates on the lettuce production submitted to different light conditions using 30, 50, 70 and 80% shading screens and an open field. The organic substrates used were Mata Pasto, Silk Flower, Jitirana, Bovine Spraying and the commercial product Basaplant (control). The experimental design was completely randomized, in a 5 x 5 factorial scheme with 4 replicates. It was observed that the protected environments reduced the average and maximum air temperature, the average and maximum luminosity and the relative humidity of the average and maximum air compared to the open field. Silk Flower and Mata-pasto products, in general, proved to be superior to other organic fertilizers. For the cultivation of lettuce in places where the temperature and the luminosities are high and the humidity of the air are low, use of screen of sombrites between 50 and 70% of shadings are the recommended ones.